THE ROLE OF BUSINESS STRATEGY IN MODERATING THE EFFECT OF ESG PERFORMANCE ON FIRM VALUE - Xaviera, Areta; Rahman, Annisaa (Universitas Bunda Mulia, 2024)
Background: The sustainability issue has become a global conversation both in society and especially in the business world. Climate change, social crises, and environmental issues pose threats to the global economy, especially for developing countries with weaker infrastructures compared to developed nations, thus necessitating sustainable practices, one of which is through ESG disclosure.Objective: This study aims to empirically examine the influence of ESG performance on firm value with business strategy using Miles & Snow's typology (1978) as a moderator.Research Methodology: This study uses unbalanced panel data regression with fixed effects using robust standard error to prevent bias in testing the formulated hypotheses. The population in this study consists of non-financial sector companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022, with a sample of 194 companies. The data collection method utilizes purposive sampling. Data is analyzed using the panel data regression method.Research Findings: The results of this study show that ESG performance has a significant negative impact on firm value. Furthermore, this research finds that business strategy can moderate the relationship between ESG performance and firm value, where it strengthens the negative relationship between ESG and firm value. Additional analysis reveals that the defender strategy weakens the negative relationship between ESG and firm value. Meanwhile, the other two strategies are unable to moderate the relationship between ESG and firm value.Originality/Novelty of Research: This is a study examining the influence of ESG on firm value with business strategy as a moderator in the non-financial sector companies in Indonesia listed on the BEI using data from 2018 to 2022